Efficacy and safety of amantadine as a treatment for apathy after brain injury: Two single-case experimental design studies. Issue 6 (3rd July 2022) - Spauwen, Peggy; Ter Mors, Bert; van Harten, Peter; Domensino, Anne-Fleur; Ponds, Rudolf; van Heugten, Caroline
ABSTRACT: Studies on the efficacy of amantadine as a treatment for apathy after brain injury are scarce and of low quality. We examined the efficacy and safety of amantadine for treatment of apathy in two individuals with brain injury. Two double-blind, randomized, single-case experimental (baseline-amantadine-placebo-withdrawal) design (SCED) studies. Apathy measures included a Visual Analogue Scale (VAS), the Neuropsychiatric Inventory (NPI) apathy subscale and the Behavior Rating Inventory of Executive Function for Adults "Initiate" subscale. Safety measures included a rating scale of possible side effects of amantadine and physical examinations. No difference in apathy symptoms (VAS) between baseline and amantadine phase was found in case 1 (NAP = 0.55). Surprisingly, in case 2, apathy symptoms deteriorated from baseline to amantadine phase (NAP = 0.28, 90% CI = −0.69 to −0.20) and improved from amantadine to placebo phase (NAP = 0.92, 90% CI = 0.60–1.00). This improvement was also found on the NPI apathy subscale. Side effects of amantadine were observed in case 2. In this SCED study, amantadine did not improve apathy symptoms in two individuals with brain injury. However, this study shows that side effects of amantadine can occur which lead to a significant decrease in well-being. More high quality studies are required.